Referentes identificatórios e jogos identitários no candomblé = Identifying references and identity games in candomblé - Nunes, Mônica de Oliveira (Ciencias sociales y religión, 2007)
In this article, we stress the importance of a set of what we call the “identitfication referents” present in the Candomblé idiom and present a discussion of the manner people use these elements to build their identities in a progressive and flexible way. With this objective in mind, we decided to reconsider some issues related to how the construction of the person is analyzed in Candomblé, starting with what classical authors had to say on the subject and emphasizing what ethnographic data produced in the city of Cachoeira, Bahia. indicates as innovations in relation to them. First, we present the controversy between unicity and multiplicity of the self in Candomblé, inserting it in the broader philosophical debate about how cultures produce different metaphors to cover a probably universal “illusion of totality”. Then, we point out to the existence of individuality mechanisms within a society we could otherwise consider as being mainly social-centric. Finally, we present new religious referents that are not generally explored in analysis regarding identity games in Candomblé, as we emphasize the importance of the adepts’ subjectivity in the construction of these games.